Development of Design Principles of Group Awareness Tool for Facilitating Computer-supported Collaborative Argumentation - Zhao, Xin (International Journal of Computer Science and Information Technology, 2024)
As one of the forms of collaborative learning, collaborative argumentation can improve students’ argumentation skills, promote effective content learning and cultivate critical thinking. Especially in the field of Computer-supported Collaborative Learning (CSCL), such as conflicts between group members, free-riding behavior, and unequal participation occur frequently. At the same time, in the CSCL environment, it is difficult to coordinate one’s actions with other group members’ actions. These problems are mainly caused by learners who cannot obtain group awareness information about accompanying learners and the current group. Therefore, this study according to the previous research, the initial design principles and initial specific guidelines for the group awareness tool were identified. After that, three educational technology experts reviewed the initial design principles and guidelines. The modified specific guidelines were applied to the two-week classroom teaching of 45 first-year students in a class. In addition, a learners’ response survey was conducted on the students who actually participated in the computer-supported collaborative argumentation activities. Finally, the results of questionnaire surveys (n=45) and interviews (n=5) were analyzed, and the final specific guidelines were developed. According to the research results, collaborative argumentation based on group awareness tool solves the problem that general collaborative argumentation activities can’t obtain timely information on the cognitive, behavioral, and social awareness of accompanying learners and the current group study situation. It can continuously maintain their study motivation and promote interaction among learners to improve the quality of computer-supported collaborative learning.